Comparison of floor and cage housing systems in terms of some welfare assessments in broiler - Ozhan, Nejla; Simsek, Ulku Gulcihan; Ozcelik, Mehtap (Ankara Univ Press, 2016)
This study was conducted to investigate simultaneously compare floor with cage housing systems in terms of some blood parameters, bone quality and pH level of Musculus pectoralis in broilers. The animal material of the study was consisted of a total of 30 broilers per housing system, having stable live weight, were selected on 32nd day of growing period. All broilers per system were choosen at six different flocks having 25.000 capacities. The chickens were slaughtered via beheading method and blood samples were collected into special tubes. The pH level of breast muscle was measured within ten minutes later following the slaughter. Bones were eviscerated from meat and analyzed in terms of physical properties and mineral levels. Serum glucose, very-low-density lipoprotein (VLDL cholesterol) and uric acid levels increased in broilers reared by cage housing systems (P<0.05). There were not any significant differences at serum total cholesterol, triglyceride, protein level and enzyme activities of alkaline phosphatase and creatine kinase (P>0.05). Ash ratios of tibio-tarsal and femora bones were lower in cage housing system (P<0.05). Dimensions and weights of tibia and femora bones were observed to have similar values between groups (P>0.05). pH levels of breast muscle was significantly higher in cage housing systems than floor system (P<0.01). Consequently, cage housing system was negatively affected on broiler's blood parameters, bone quality and pH level of breast muscle.
Yer ve kafes sistemlerinin etlik piliçlerde bazı refah parametreleri bakımından karşılaştırılması
Keywords: Broiler; cage housing; floor housing; welfare